In a house of lies - Rankin, Ian (Rankin, Ian. Inspector Rebus novel series, 2018)
A missing private investigator is found locked in a car hidden deep in the woods. Worse still - both for his family and the police - the body was in an area that had already been searched 10 years ago. Detective Inspector Siobhan Clarke is part of a new inquiry, combing through the mistakes of the original case. There were always suspicions over how the investigation was handled, and now - after a decade without answers - it's time for the truth. Every officer involved must be questioned, and it seems everyone on the case has something to hide - and everything to lose. None more so than Detective John Rebus.